Perancangan dan Pengembangan Produk Helm Menggunakan Metode Quality Function Deployment (QFD) - Rossi Septy Wahyuni; Eko Nursubiyantoro; Gina Awaliah (OPSI, 2020)
Helmet is a product that is generally used when riding a motorcycle, the function of the helmet is to protect body parts especially the head when accident while driving. Many of helmet product still have deficiency both in terms of form of function, in this case helmet products still have any problems in their function. The shape of the helmet that is already on the market does not pay attention to the needs of the community if the helmet is exposed to rain when stored in the outdoor. The planning and development of helmet products is then processed using Quality Function Development (QFD). The customer need regarding customer products are half face shaped helmet, full face shaped helmet, flip up shaped helmet, lightweight helmet shell materials, strong helmet shell materials, strong helmet locking locks, visor material is not easily scratched, visor material is not easily broken, visor material is not easily to blur, foam helmet is easily to clean, foam helmet is soft, foam helmet is not easily to moldy, cloth helmet is soft on the face, helmet cloth is easily to absorb sweat, cloth helmet is not easy to smell, helmet lock is easy to install, helmet in solid colour, helmet with patterned appearance, and helmet there are added feature waterproof. The technical characteristics of helmet product are the type of the shell material, the shape of the shell, the weight of the shell, the colour of the shell, the type of visor material, the colour of the visor, the type of foam material, the type of fabric material, the type of locking material, and additional features of waterproof helmet. The specification of the proposed helmet are the type of shell material in the form of ABS plastic, the shape of the helmet is half face, the weight of the helmet is 2 kg, the colour of the helmet is solid (black), the type of the visor is polycarbonate, the colour of the visor is transparent, the type of material foam is polystyrene, the type of fabric is the velor fabric, the type of locking material is quick release buckle, and additional feature are waterproof in the form of cover of taslan fabric.